Anisotropic thermoelectric figure-of-merit in Mg3Sb2. (June 2020) - Meng, F.; Sun, S.; Ma, J.; Chronister, C.; He, J.; Li, W.
Abstract: In view of the tensor nature of thermoelectric (TE) figure of merit ZT, the lack of experimental data on its anisotropic transport properties, and the recent advances in theoretical modeling, here we calculated the TE properties of n -type and p -type Mg3 Sb2 as a function of temperature along major crystallographic axes using a parameter-free first principles algorithm of electron–phonon interactions and phonon-phonon interactions limited Boltzmann transport equations for charge carriers and phonons, respectively. The calculated ZT curves of n -type Mg3 Sb2 are found to be nearly isotropic, and the highest calculated ZT is about 2.1 at 750 K, in reasonable agreement with the experimental results and thus validating our calculations. In contrast, we found strong anisotropy of ZT in p -type Mg3 Sb2, with the highest calculated ZT value attaining 1.5 at 750 K along the c -axis and 0.6 in the ab -plane at 750 K, respectively. The strong anisotropy in p -type ZT is mainly dominated by the electrical conductivity along different directions which relies on the anisotropic charge carrier effective mass. In light of the fact that the experimentally measured ZT values are less than unity in polycrystalline p -type Mg3 Sb2, these results attest the key role of texture in the performance improvement of polycrystalline p -type Mg3 Sb2 so as to mitigate the performance imbalance between the n -type and p -type Mg3 Sb2 legs toward higher device performance. Graphical abstract: Image 1 Highlights: Thermoelectric properties of Mg3 Sb2 are studied by solving BTE with electron(phonon)-phonon interactions from ab initio . The calculated electrical and phonon transport properties of n -Mg3 Sb2 agree with experiments, validating our calculations. The ZT of p -Mg3 Sb2 is strongly anisotropic, with a state-of-the-art ZT 1.5 along c -axis at 750 K. The anisotropy in the ZT of p -Mg3 Sb2 suggests texture can play a key role in ZT improvement of polycrystalline p -Mg3 Sb2 .